MAPPADENDANG: MUSIK UPACARA PESTA PANENMASYARAKATBUGIS TOLOTANG - Sriwahyuni, Sriwahyuni (Institut Seni Indonesia Yogyakarta, 2013)
The harvest ceremony ofthe Bugis Tolotang people expressed a gratitude toward the DewataE,the goddess. The Mappadendang musical performance of the ceremony, was attended by the entire community of Bugis Tolotang in Amparitta Sidrap, South Sulawesi province. The main concern of this study is to investigate some meanings implied in the performance which is aimed atunderstanding contextual interpretation of the music. This study utilizes qualitative method where field data are described analytically. Data were collectedthrough interviews, observation and participant observation techniques. This study found that the music uses two contrasting tempos and dynamics, medium and fast, as well as medium loud and loud. The three rhythmical patterns of the music are,1) the pa'dekko by the theindo'na, 2) the ma'dupa si'di and 3) the ma'dupa dua, by ambo'na. These symbols expresses the disclosure of people’s religious emotion.Keywords: Mappadendang, Bugis Tolotang, musical meaning